42. Functional Tremor: When neurophysiology makes the difference. Issue 12 (December 2017) - Parenti, L.; Barloscio, D.; Priori, A.; Bartolotta, M.; Sartucci, F.; Bocci, T.
Abstract : Functional tremor (FT) still remains a challenge for clinicians; here, we propose a simple and fast test battery for an early diagnosis of FT. We enrolled ten patients with probable FT and compared them with patients with essential tremor (ET) or tremor-dominant Parkinson's Disease (PD). Surface polymyography was bilaterally performed with arms relaxed, with arms outstretched at shoulder level without or with a 500-g mass attached to the wrist ("mass loading"), during voluntary contralateral motor activation and while performing ballistic movements. We also asked to the patient to use the index finger of the left hand to tap in time with a metronome at rates of 1, 3 and 5 Hz. At the end of the test, we recorded Blink Reflex Habituation. Polymyography revealed (a) a paradoxical increase of tremor amplitude with mass loading, (b) jerks' synchronization between antagonistic muscles performing voluntary contralateral motor activation and (c) tremor inhibition during a ballistic movement. Co-activation sign was present. Finally, all the patients showed a Blink-Reflex habituation preserved. Our results prompt further studies to integrate clinical and electrodiagnostic criteria in the whole field of hyperkinetic movement disorders, exploring the floating border between organic and functional disease.